Differences in the perception of young compared to old managers - Grandl, Stefan Alexander (2016)
Age bias research emphasizes systematic cognitive processes which influence the perception towards others automatically. An online survey among 195 U.S.-American employees was conducted to determine whether there is a difference in employee perceptions towards young and old managers. The collected data shows (a) differences in the perception of young compared to old managers. In addition the study examines if (b) the perception of employees from different generations towards their out or in-groups is heterogeneous. The measures included perceptions of employees regarding the employees’ connectedness to an old or young manager. Furthermore the extent of employees age stereotyping (competence/warmth) towards managers was measured. Data was analysed with a GLM test to investigate the differences of the employees’ perceptions Data supported both hypotheses (a) and (b).